2006
DOI: 10.1210/me.2004-0075
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase Stimulates Estrogen-Mediated Transcription and Proliferation through the Phosphorylation and Potentiation of the p160 Coactivator Glucocorticoid Receptor-Interacting Protein 1

Abstract: Nuclear hormone receptors, such as the estrogen receptors (ERs), are regulated by specific kinase signaling pathways. Here, we demonstrate that the p38 MAPK stimulates both ERalpha- and ERbeta-mediated transcription in MCF-7 breast carcinoma, Ishikawa endometrial adenocarcinoma, and human embryonic kidney 293 cells. Inhibition of this potentiation using the p38 inhibitor, RWJ67657, blocked estrogen-mediated transcription and proliferation. Activated ERs promote gene expression in part through the recruitment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…Additional mechanisms resulting from decreased activity of MAPK pathways (p38 MAPK and ERK1/2) (Figures 4 and 10) may have also contributed to the DPI-induced G 1 checkpoint. While the role of ERK1/2 in proliferation is well established and works downstream of many stimuli, including growth factors and hormones (Yoon and Seger, 2006), p38 MAPK has often been associated with stress responses (Dent et al, 2003); however, p38 MAPK has also been shown to promote proliferation in a variety of cell types (Juretic et al, 2001;Frigo et al, 2006). Common (for example, c-jun, c-fos) and numerous distinct substrates have been identified as targets of ERK1/2 and p38 MAPK activity (Ono and Han, 2000;Yoon and Seger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanisms resulting from decreased activity of MAPK pathways (p38 MAPK and ERK1/2) (Figures 4 and 10) may have also contributed to the DPI-induced G 1 checkpoint. While the role of ERK1/2 in proliferation is well established and works downstream of many stimuli, including growth factors and hormones (Yoon and Seger, 2006), p38 MAPK has often been associated with stress responses (Dent et al, 2003); however, p38 MAPK has also been shown to promote proliferation in a variety of cell types (Juretic et al, 2001;Frigo et al, 2006). Common (for example, c-jun, c-fos) and numerous distinct substrates have been identified as targets of ERK1/2 and p38 MAPK activity (Ono and Han, 2000;Yoon and Seger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The α isoform is the most abundant and is subject to a larger inter-individual variability than the other three isoforms (12). P38 MAPK plays a complex role in the regulation of cell growth, differentiation, apoptosis, and responses to inflammation or stress (4,5). P38 MAPK activity was found to be upregulated in breast, head and neck carcinomas, lymphomas, gliomas and squamous cell carcinomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experimental modulation in these pathways in response to treatment with selective estrogen receptor modulators is associated with growth inhibition of MCF-7 cells both in in vitro cell cultures as well as in in vivo xeno-transplant models for tumorigenecity via multiple mechanisms (12,13,22,23,25,26). These data taken together, suggest that the mode of action of Taheebo is similar to that of a selective estrogen receptor modulator.…”
Section: A ----------------------------------------------------------mentioning
confidence: 86%
“…Regarding the effect of Taheebo on ER signaling, it was observed that Taheebo treatment up-regulated the dual specific phosphatase (DUSP) gene family is responsible for negative regulation of MAPK signaling (22)(23)(24). These data indicate that Taheebo suppresses the proliferation of ER + MCF-7 cells via its effect on the ligand independent AF-1 domain that is critical for the ER signaling pathway.…”
Section: A ----------------------------------------------------------mentioning
confidence: 97%